PENGARUH PENGETAHUAN KEWIRAUSAHAAN, KARAKTERISTIK DAN KETERAMPILAN WIRAUSAHA TERHADAP KEBERHASILAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN PONOROGO - Praiswara, Rifkhi; Wijianto; Chamidah, Siti (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to identify and explain the influence of entrepreneurial knowledge, entrepreneurial characteristics, and entrepreneurial skills on the success of Micro, Small, and Medium Enterprises (MSMEs) in Ponorogo Regency. The research method used in this study is quantitative. The population consists of MSME owners in Ponorogo Regency. The sampling technique applied is purposive sampling, with a total sample of 100 respondents. The data analysis technique used in this research is multiple linear regression analysis. The results of the study indicate that: (1) entrepreneurial knowledge has a positive and significant effect on business success; (2) entrepreneurial characteristics have a positive and significant effect on business success; (3) entrepreneurial skills have a positive and significant effect on business success; and (4) entrepreneurial knowledge, entrepreneurial characteristics, and entrepreneurial skills simultaneously have a positive and significant effect on the success of MSMEs in Ponorogo Regency.